Impacts of Air Velocity Treatments Under Summer Conditions: Part III—Litter Characteristics, Ammonia Emissions, and Leg Health of Heavy Broilers - Derek West; Suraiya Akter; Bin Cheng; Edgar Oviedo; John Classen; Lingjuan Wang-Li (Animals)
The broiler industry is crucial for rural economies, but it faces challenges in enhancing animal performance and well-being, particularly due to heat stress and ammonia (NH3) in grow-out houses. This study investigates the effectiveness of air velocity (AV) treatment in reducing heat stress and NH3 emissions while also improving litter conditions to enhance animal welfare. Conducted at the North Carolina State University’s poultry engineering laboratory, the research used six identical controlled chambers, exposing broilers to High and Low AV treatments from 28 to 61 days across four flocks during the summers of 2017 and 2018. The nitrogen mass balance (NMB) method quantified NH3 emissions, while litter quality was assessed for moisture content, pH, total nitrogen, and total ammoniacal nitrogen. Additionally, leg health was evaluated through assessments of footpad dermatitis (FPD) and hock burns (HB) at 42 and 61 days. Results showed higher NH3 emissions in Low AV chambers, while High AV conditions improved litter quality and resulted in greater nitrogen retention. Broilers in High AV chambers also had higher individual body weights and better leg health scores. Thus, optimizing AV effectively mitigates heat stress, controls NH3 emissions, and enhances overall broiler performance and welfare, offering insights for sustainable industry practices.